Packaging dan Brand Ambassador: Dampaknya Pada Keputusan Pembelian Konsumen - Tannady, Alvin; Syauqi, Teuku Muhammad; Sahputra, Ngatno (Bisnis-Net, 2024)
This study focuses on the influence of Product Packaging and Brand Ambassadors on the Purchasing Decisions of Consumers at PT. Motto Beringin Abadi Indonesia (Scarlett Products) in Medan. The research methodology involves the collection of quantitative data through surveys and questionnaires and data analysis using multiple regression tests and hypotheses using SPSS V. 25. The results show a positive and significant effect of Product Packaging and Brand Ambassadors on purchasing decisions. The statistical parameters show the t-count value for Product Packaging and Brand Ambassadors (2.206 and 3.223) is greater than the t-table (1.974) with a significance of 0.000 < 0.05. The simultaneous test indicates that both factors influence purchasing decisions with F-count greater than the F-table (112.445 ˃ 3.05) and a significance value (0.000 ˂ 0.05). The determination test shows that 58.1% of consumer purchasing decisions are influenced by Product Packaging and Brand Ambassadors while the remaining 41.9% is influenced by other variables not examined in this study.